The Moderating Effects of Past Change Experience on the Relationship Between Change Related Self-Efficacy and Employee Commitment to Change - Jameri, Aszahari Mohamad; Noranee, Shereen; Nik Abdullah, Nik Herda (Indonesian Journal of Economics, Social, and Humanities, 2025)
Organizational change is a common occurrence in today's dynamic business environment, and employee commitment plays a crucial role in its successful implementation. However, the factors influencing employee commitment and the role of past change experience in this process are underexplored in the context of Malaysian Government-Linked Investment Companies (GLICs). This paper aims to propose a conceptual framework for the moderating effects of past change experience on the relationship between change related self-efficacy on employee commitment towards organizational change in Malaysian GLICs. This paper employs a qualitative approach by reviewing all pertinent literature on the subject from various databases and relating it to the current environment, which attempts to bring the entire concept of organizational change into focus based on the findings of previous research and a proposed conceptual framework that can be used for future research. This research will contribute to the existing body of knowledge by providing a thorough comprehension of the factors of change related to self-efficacy influencing employee commitment towards organizational change. The findings will have practical implications for GLIC leaders and change managers, providing insights on how to effectively engage employees during periods of change, increase their commitment, and ultimately increase the success of organisational change initiatives.